Separate and unequal : the inside story of Israeli rule in East Jerusalem - Cheshin, Amir; Hutman, Bill; Melamed, Avi (Harvard University Press, 1999)
This text discloses the details of Israel's discriminatory policies towards Jerusalem Arabs and shows how Israeli leaders mishandled everything form security and housing to schools and sanitation services, to the detriment of not only the Palestinian residentrs but also Israel's own agenda.